Systema naturae IN THE PLANT KINGDOM OF THE 21st CENTURY: WHAT HAS BEEN DISCOVERED IN MEXICO? ¿QUÉ SE HA DESCUBIERTO EN MÉXICO? - Chan Quijano, José Guadalupe; Martínez Meléndez, Nayely (Kuxulkab', 2024)
Linnaeus' Systema naturae was one of the most important classification systems in the history of human beings, since a first and last name was given to every living being and in the case of flora he managed to classify approximately 6,000 species. The beginning of this classification managed to lay the fundamental foundations for many researchers to develop more specific nomenclatures for the different family groups of plant species. Furthermore, in the 21st century, new species continue to be found for Mexico. Therefore, this work articulates the contribution that Linnaeus made to the botany of Mexico.
Keywords: Botany; Systematic; Nomenclature; Taxonomy; Plantae